(untitled) (Ideal Journal of Multidisciplinary Research, 2026)
This article presents a linguocultural analysis of somatic phraseological units-expressions that incorporate body-related terminology and reflect cultural meanings associated with the human body. By examining idiomatic phrases across different languages, the study reveals how somatic expressions encapsulate cultural beliefs, values, and social norms. The analysis highlights the interplay between language and culture, demonstrating how bodily references in idioms serve as windows into the collective psyche of a society. Through comparative analysis, the article identifies common themes and unique cultural nuances in somatic phraseology, contributing to a deeper understanding of how language shapes and reflects cultural identity.